Cyber warfare : military cross-border computer network operations under international law / Johann-Christoph Woltag. - Woltag, Johann-Christoph (International law (Antwerp, Belgium) ;, 2014)
In the last five years the topic of cyber warfare has received much attention due to several so-called "cyber incidents" which have been qualified by many as State-sponsored cyber attacks. This book identifies rules and limits of cross-border computer network operations for which States bear the international responsibility during both peace and war. It consequently addresses questions on jus ad bellum and jus in bello in addition to State responsibility. By reference to treaty and customary international law, actual case studies (Estonia, Georgia, Stuxnet) and the Tallinn Manual, the author illustrates the applicability of current international law and argues for an obligation on the State to prevent malicious operations emanating from networks within their jurisdiction.This book is written for academics in public international law and practitioners from the military and other public security sectors.